2006
DOI: 10.1242/jcs.03207
|View full text |Cite
|
Sign up to set email alerts
|

Cell-cycle-dependent dynamics of nuclear pores: pore-free islands and lamins

Abstract: Nuclear pores are sophisticated gateways on the nuclear envelope that control macromolecular transport between the cytoplasm and nucleoplasm. So far the structural and functional aspects of nuclear pores have been extensively studied, but their distribution and density, which might reflect nuclear organization and function, remain unknown. Here, we report the cell-cycle-dependent dynamics of nuclear pores. Large distinct subdomains lacking nuclear pores are present on the nuclear surface of HeLaS3 cells in ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
143
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(156 citation statements)
references
References 61 publications
13
143
0
Order By: Relevance
“…Doublelabeled nuclei of fixed and permeabilized HeLa cells revealed that the immunofluorescence staining of NE protein markers distributed in characteristic patterns showing variable degrees of overlap ( Fig. 1), indicative of the existence of partially overlapping networks of NE proteins, consistent with previous studies (Liu et al, 2007;Lu et al, 2008;Maeshima et al, 2006;Shimi et al, 2008). We determined the degree of colocalization statistically by Pearson analysis using dual-channel image data from an optical plane corresponding to the lower nuclear surface.…”
Section: Samp1 Distributes In Distinct Micro-domains Of the Inner Nucsupporting
confidence: 82%
See 1 more Smart Citation
“…Doublelabeled nuclei of fixed and permeabilized HeLa cells revealed that the immunofluorescence staining of NE protein markers distributed in characteristic patterns showing variable degrees of overlap ( Fig. 1), indicative of the existence of partially overlapping networks of NE proteins, consistent with previous studies (Liu et al, 2007;Lu et al, 2008;Maeshima et al, 2006;Shimi et al, 2008). We determined the degree of colocalization statistically by Pearson analysis using dual-channel image data from an optical plane corresponding to the lower nuclear surface.…”
Section: Samp1 Distributes In Distinct Micro-domains Of the Inner Nucsupporting
confidence: 82%
“…Investigations in different labs have shown that proteins of the nuclear lamina and the inner nuclear membrane are not evenly localized in the periphery of mammalian nuclei, but instead distribute in distinct but overlapping networks in the NE (Liu et al, 2007;Lu et al, 2008;Maeshima et al, 2006;Shimi et al, 2008). These networks might serve as scaffolds or fundaments for the assembly of a large variety of functional micro domains.…”
Section: Introductionmentioning
confidence: 99%
“…There is now strong evidence of an intimate link between the distribution of nuclear pores and the organisation of nuclear structures and processes. [34][35][36] According to our data, the nuclear pores in Leishmania exhibit a striking punctuated distribution, defining a reduced and relatively constant number of 'domains' at the nuclear periphery. This contrasts, however, with previous serial sectioning EM data that allowed Rout and Field 37 to identify 200 -300 nuclear pores per nucleus in T. brucei.…”
Section: Discussionsupporting
confidence: 53%
“…28 However, the NPC density in replicative senescent cells was much higher, even though both the quiescent and senescent cells were in a nondividing state. 28 This is not so surprising because the proliferation signaling (Ras/ Erk) activates Cdks.…”
Section: Npc Formation Nuclear Growth and Tumor Cellsmentioning
confidence: 96%